Relationship between serum irisin level, all-cause mortality, and cardiovascular mortality in peritoneal dialysis patients - Sijia Zhou; Wen Tang; Xiaoxiao Wang; Qingfeng Han; Qiong Bai; Aihua Zhang (Karger Publishers, 2023)
Introduction: This study aimed to investigate the prospective role of serum irisin-a novel adipo-myokine-in all-cause mortality and cardiovascular (CV) mortality in patients on peritoneal dialysis (PD). Methods: A prospectively observational study was conducted with 154 PD patients. Baseline clinical data were collected from the medical records. Serum irisin concentrations were determined using enzyme-linked immunosorbent assay. Patients were divided into the high irisin group (serum irisin ≥ 113.5ng/mL) and the low irisin group (serum irisin < 113.5ng/mL) based on the median value of serum irisin. A Body Composition Monitor was used to monitor body composition. Cox regression analysis was utilized to find the independent risk factors of all-cause and CV mortality in PD patients. Results: The median serum irisin concentration was 113.5 ng/mL (interquartile range, 106.2-119.8 ng/mL). Patients in the high irisin group had significantly higher muscle mass and carbon dioxide combining power (CO2CP) than those in the low irisin group (p < 0.05). Serum irisin was positively correlated with pulse pressure, CO2CP, and muscle mass, while negatively correlated with body fat percentage (p < 0.05). During a median of follow-up for 60.0 months, there were 55 all-cause deaths and 26 CV deaths. Patients in high irisin group demonstrated a higher CV survival rate than those in low irisin group (p = 0.016). Multivariate Cox regression analysis showed that high irisin level [hazard ratio (HR), 0.341; 95% confidence interval (CI), 0.135-0.858; p = 0.022], age, and diabetic mellitus were independently associated with CV mortality in PD patients. However, serum irisin level failed to demonstrate a statistically significant relationship with all-cause mortality. Conclusion: Low serum irisin levels at baseline were independently predictive of CV mortality but not all-cause mortality in PD patients. Therefore, serum irisin could be a potential target for monitoring CV outcomes in PD patients.